Perspective matters: assessment of medical students' communication and interpersonal skills by simulated patients from the internal and external patient perspective - Prediger, Sarah; Harendza, Sigrid (GMS Journal for Medical Education, 2021)
Background: Communication and interpersonals skills are important qualities of professionalism in medicine. In medical curricula, they are usually acquired in communication trainings and assessed in OSCEs. Studies show correlations as well as differences between communication ratings of examiners and simulated patients. In our study, simulated patients assessed medical students’ communication and interpersonal skills after a consultation hour from the internal and the external patient perspective.Methods: In December 2019, 52 final-year medical students participated in a consultation hour as part of a simulated first day of residency assessment. They were assessed twice with a questionnaire for communication and interpersonal skills (ComCare) by the simulated patients: All eight ComCare items were assessed on a five-point Likert scale (1=full disagreement to 5=full agreement). Differences between the item means of internal and external perspective were examined by paired t-tests. Results: Overall, significantly higher ratings were found for all ComCare items from the external perspective except for the item “Interest”. Ratings for the items “Language” and “Listening” were significantly higher from the external perspective for all simulated patients. Significantly higher ratings for all items from the external perspective were observed for two simulated patients.Conclusion: Simulated patients’ ratings after a conversation seem to represent a more authentic view on students’ communication and interpersonal skills because of the emotionally experienced situation. The evaluation of those skills from a simulated patient perspective could be a valuable complement to communication ratings by examiners.